2020
DOI: 10.3389/fpsyg.2020.543282
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leaders’ Coaching Behaviors on Employee Learning Orientation: A Regulatory Focus Perspective

Abstract: Although scholars have recognized leaders' importance in facilitating employee learning, the potential role that leaders' specific behaviors play in followers' learning outcomes remains elusive. Based on the literature, we identified two styles of leaders' coaching behaviors that may promote followers' learning, namely encourage-to-explore behaviors and guide-to-learn behaviors. We expect that these two styles of coaching behaviors would have different relationships with employee learning orientation, moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 77 publications
(133 reference statements)
4
29
0
Order By: Relevance
“…The present research indicates the importance of role modeling (Bandura, 1986(Bandura, , 2004Gibson, 2004;Wood and Bandura, 1989) in facilitating state LGO. Although previous studies have found a positive influence of LGO training (Noordzij et al, 2013), mastery-approach goal structure (Michou et al, 2013) and leader's coaching behaviors (Liu and Xiang, 2020) on LGO, this study may be the first to identify the effect of role modeling as an antecedent of LGO.…”
Section: Theoretical Implicationsmentioning
confidence: 77%
See 2 more Smart Citations
“…The present research indicates the importance of role modeling (Bandura, 1986(Bandura, , 2004Gibson, 2004;Wood and Bandura, 1989) in facilitating state LGO. Although previous studies have found a positive influence of LGO training (Noordzij et al, 2013), mastery-approach goal structure (Michou et al, 2013) and leader's coaching behaviors (Liu and Xiang, 2020) on LGO, this study may be the first to identify the effect of role modeling as an antecedent of LGO.…”
Section: Theoretical Implicationsmentioning
confidence: 77%
“…Chi and Huang (2014) reported that transformative leadership enhances team LGO, implying that leadership may promote employees' state LGO. Liu and Xiang (2020) also found that leader-coaching behaviors had a positive effect on employee-state LGO. Notably, Vandewalle et al (2019) stated that leaders could help followers enhance their LGO by acting as role models.…”
Section: Workplace Role Modelingmentioning
confidence: 83%
See 1 more Smart Citation
“…Employees' learning effects refer to the extent to which an individual uses the knowledge and skills acquired to perform tasks and improve work processes and work performance in the workplace (Matsuo, 2018). Supervisors' leadership behavior has a positive impact on subordinates' learning effects (Gray, 2006;Liu and Xiang, 2020). Therefore, based on the path-goal theory, we predict that managerial coaching behavior is positively associated with subordinates' learning effects.…”
Section: Managerial Coaching Behavior and Learning Effectsmentioning
confidence: 96%
“…Encouraging employee learning behavior is a constructive way to accumulate more knowledge to help companies to stand out in the highly competitive market. Employee learning behavior thus has often been regarded as a useful route toward organizational competitiveness and excellence (Maurer and Tarulli, 1994; Liu and Xiang, 2020). Studies confirmed that the companies with more learning behaviors among employees can indeed get a higher profit and more organizational innovation (Yang and Konrad, 2011), and build better relationships with customers and suppliers (Dimovski and Skerlavaj, 2005; Škerlavaj et al , 2007).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%